Study Eksperimen: Pengaruh Gaya Kepemimpinan Terhadap Psychological Safety - SITI RODIAH; Agustiawan Agustiawan (Faculty of Economics and Business Universitas Muhammadiyah Riau, 2019)
This study aims to compare the two leadership styles, namely transformational (intellectual stimulation and inspirational motivation) and transactional (contingency reward and MBE Active) in influencing psychological safety by using a 2 x 2 experimental design beetwen subject. The sample in this study were accounting students of the University of Muhammadiyah Riau force 2016 who took courses in management accounting and management control systems. Based on the results of hypothesis testing conducted using an independent sample t-test, it was found that managers who have superiors who have intellectual stimulation and contingency reward will be free to express their problems to superiors (psychological safety) compared to managers who have superiors with an inspirational motivation and MBE Active style. The results of this study are expected to improve the psychological safety of managers and all staff employees in a company to express their problems without fear and anxiety so that the company's goals can be achieved.